2022
DOI: 10.1101/2022.05.16.491946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insertions and deletions mediated functional divergence of Rossmann fold enzymes

Abstract: Nucleobase-containing coenzymes are considered the relics of an early RNA-based world that preceded the emergence of protein domains. Despite the importance of coenzyme-protein synergisms, their emergence and evolution remain poorly understood. An excellent target to address this issue is the Rossman fold, the most catalytically diverse and abundant protein architecture in Nature. Here, we investigatedted the two largest Rossman lineages, namely the nicotinamide adenine dinucleotide phosphate (NAD(P))-binding … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The final alignment to perform the chimera building was obtained by filtering according to sequence identity, the highest sequence identity (12%) for the longest aligned fragments with the smallest RMSD (2.6 Å) using default parameters. In summary, we performed a customized version of the protocol used to build the Fuzzle database [13,34,35].…”
Section: Methodsmentioning
confidence: 99%
“…The final alignment to perform the chimera building was obtained by filtering according to sequence identity, the highest sequence identity (12%) for the longest aligned fragments with the smallest RMSD (2.6 Å) using default parameters. In summary, we performed a customized version of the protocol used to build the Fuzzle database [13,34,35].…”
Section: Methodsmentioning
confidence: 99%
“…While their utilization in protein engineering is infrequent due to their tendency to be highly deleterious, often resulting in frame-shift mutations that significantly alter the protein sequence or prematurely terminate translation, there is evidence suggesting potential benefits. Instances of altered protein functionality through insertions and deletions have been reported, such as the broadening of substrate specificity in β-lactamase [91] and the modification of coenzyme specificity in Rossman fold enzymes [92]. These findings underscore the need for further exploration and investigation into the potential applications of this approach in protein engineering.…”
Section: Random Insertion and Deletionmentioning
confidence: 99%
“…Intuitively, the evolution of a new protein function is bound to necessitate a certain degree of active site reconfiguration to accommodate a novel substrate or ligand, particularly if an enzyme evolves a new chemical reaction such as the cleavage of a different chemical bond . Compared to substitutions, indels may offer greater potential for such a task, by facilitating the swift acquisition of novel structural features that enable ligand recognition, novel catalysis, or new protein–protein interactions. ,, For instance, Toledo-Patiño et al recently demonstrated how indels could have triggered a switch in coenzyme specificity (NAD­(P)- vs SAM-binding) during the evolutionary divergence of two Rossmann lineages …”
Section: Indels Engines Of Functional Innovationlessons From Natural...mentioning
confidence: 99%
“…46,49,78 For instance, Toledo-Patinõ et al recently demonstrated how indels could have triggered a switch in coenzyme specificity (NAD(P)-vs SAM-binding) during the evolutionary divergence of two Rossmann lineages. 79 The study of protein superfamilies remains limited, however, to the observation of evolutionary end points that diverged millions, or billions, of years ago. A closer look at the mechanisms underlying protein evolution in nature can further delineate the role played by indels in functional innovation.…”
Section: Innovation�lessons From Natural Evolutionmentioning
confidence: 99%